Development of Nursing Care Plan for Severe Head Injury Patients in Surgical Intensive Unit, Surin Hospital - Sornsurin, Lackana (Journal of Health Science of Thailand, 2017)
This study was aimed at developing nursing care plan for severe head injury patients in surgical intensive care unit and outcomes of care plan for severe head injury, Surin hospital. An operational research was described in two phases; pre-operational and operational. The pre-operational phase included nursing care plan protocol for severe head injury patients in a surgical intensive unit looked after by fourteen registered nurses. The patients were eleven severe head injury patients (GCS 3 - 8 points) with no other injury admitted to the hospital from August 1 to September 30, 2008. The care plan was then assessed based on practitioner’s adherence, level of practitioner’s satisfaction to the care plan protocol and clinical outcome. In the operational phase; problems found during the care plan protocol application were solved by team participation. The care plan protocol was developed and applied by sixteen registered nurses to provide nursing care for thirty-one severe head injury patients with no other injury admitted to the hospital during November 1, 2008 – March 31, 2009. Level of practitioner and patient’s satisfaction to the care plan protocol and clinical outcome assessment were presented in frequency, percentage and standard deviation. The application of the nursing care plan for severe head injury patients (nine items of preoperational phase and eleven items of operational phase) showed that the pre-operational phase had the average of ventilator support of 7.22 days, average length of stay in surgical intensive care unit 6.72 days and respiratory tract infection rate 27.3 percent. While the operational phase had the average of ventilator support of 3.94 days, average length of stay in surgical intensive care unit of 4.94 days and respiratory tract infection rate of 12.9 percent. The average score of practitioner satisfaction to the care plan protocol 4.18, average of patient’s satisfaction to the care plan protocol 3.94 In conclusion, this study was a systematic care plan development which integrated nursing care, operational tools including continuous assessment. Consequently the developed nursing care plan decreased patient’s complications, length of stay, direct and indirect medical cost along with patient and family’s satisfaction.